2002
DOI: 10.1080/13668790220146456
|View full text |Cite
|
Sign up to set email alerts
|

Mirrors and Metaphors: Contemporary Narratives of the Wolf in Minnesota

Abstract: This article serves as a case study of how contemporary residents of the Upper Great Lakes states debate the ethics and meanings of living with wolves. An overview of the challenges facing Minnesota wolf management is provided, and the results of a Q-methodology study are presented. The study revealed three primary factors, or shared belief systems, about wolf management in Minnesota. The idealist perspective tells a redemption story of sin and atonement, the institutional perspective endorses scienti c manage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Different parties in the conflict can be typically defined (Byrd 2002;Mech and Boitani 2003). Those who are acquainted with wolf conflicts have suggested that the best way to solve these conflicts is often through "a loud and messy" democratic process.…”
Section: Conclusion and Practical Suggestionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Different parties in the conflict can be typically defined (Byrd 2002;Mech and Boitani 2003). Those who are acquainted with wolf conflicts have suggested that the best way to solve these conflicts is often through "a loud and messy" democratic process.…”
Section: Conclusion and Practical Suggestionsmentioning
confidence: 99%
“…Debate around the wolf is related to its abundance. As soon as population increases, conflicts with humans become increasingly likely (Bangs and Fritts 1996;Nie 2001;Byrd 2002;Treves and Karanth 2003;Mech and Boitani 2003). Examples from different regions of the world show clearly how challenging it is to find a widely accepted management policy for the species (Bjerke et al 1998;Linnell et al 2001;Mech and Boitani 2003).…”
Section: Introductionmentioning
confidence: 98%
“…A number of investigators has used Q method to explore perspectives of people involved in environmental issues (e.g. ; Steelman and Maquire 1999;Byrd 2002;Mattson et al 2006;Peter-Contesse et al 2010). The instrumental and analytical basis of Q method is the Q sort, in which participants ''map'' their own views by ranking a number of statements about the subject matter under investigation, followed by factor analysis of statements as sorted by all participants (Brown 1980).…”
Section: Q Methodsmentioning
confidence: 99%
“…Previous studies have amply documented this phenomenon, which arose not only from a culture shared among hunters and agency personnel, but also from agency reliance for revenues on hunting-related taxes and license sales, and decision making buffered from the influences of elected officials by appointed boards or commissions (Decker et al 1996;Gill 1996Gill , 2001Byrd 2002;Nie 2004;Clark and Rutherford 2005;Jacobson and Decker 2006). All aspects of routine state-level wildlife decision making, from intelligence to termination, were sequestered from electoral processes and comparatively unresponsive to those, such as AW Foes, who pursued ''nonconsumptive'' interests in wildlife.…”
Section: Management Doctrinesmentioning
confidence: 98%